Comparing sporting nations: Theory and method - Dowling, M.; Harris, S. (Meyer & Meyer Sport (UK) Ltd., 2021)
It is the essence of human nature to compare, and nowhere are comparisons more commonplace than in sport. This book focuses specifically on the comparison of sporting nations. Making meaningful comparisons (i.e. comparing the similarities and differences between social phenomena based upon empirical observation) is difficult and resource intensive and faces a host of methodological limitations, trade-offs and practical compromises. Despite these ongoing issues, there remains no introductory texts that outline the philosophical, methodological and practical challenges of comparative analysis as it applies to sport. This book is therefore the first of its kind to provide a comprehensive overview of the theory and method of comparing sporting nations illustrated through specific examples and case studies drawn from the comparative elite sport policy/management domain. In doing so, the book provides an important point of departure and reference for anyone seeking to making comparisons and to generate more focus and attention towards the logic of comparative inquiry and methodology within sport.